Mercury Methylation in Oxic Sub-Polar Marine Regions Linked with Nitrification - Despins, Marissa Collins (CORE Scholar, 2022)
Methylmercury (MeHg) is a neurotoxin that bioaccumulates to potentially harmful concentrations in Arctic marine wildlife and in those that consume them. Monitoring and modeling MeHg bioaccumulation and biogeochemical cycling in the ocean requires understanding of the mechanisms behind net mercury (Hg) methylation. The key functional gene for Hg methylation, hgcAB, is widely distributed throughout ocean basins and spans multiple microbial phyla. While multiple microbially-mediated anaerobic pathways for Hg methylation are known, in the ocean, the majority of hgcA homologs have been found in oxic subsurface waters, in contrast to other ecosystems. In particular, microaerophilic Nitrospina, a genera of nitrite-oxidizing bacteria containing a hgcA-like sequence, has been proposed as a potentially important Hg methylator in upper ocean waters. The objective of this work was therefore to examine the potential of nitrifiers as Hg methylators and quantify total Hg and MeHg across three Arctic Seas (the Gulf of Alaska, the Bering Sea and the Chukchi Sea) in regions where Nitrospina are likely present. In Spring 2021, samples for Hg analysis were obtained from all sites with a trace metal clean rosette. Hg methylation rates were quantified in concert with nitrification rates using on-board incubation experiments with Hg and 15NH4+ stable isotope additions. A significant correlation between Hg methylation and nitrification was observed across all sites, with the strongest correlation in the Chukchi Sea. Nitrospina-specific hgcA-like genes were detected at all sites. This study, linking Hg methylation and nitrification in oxic seawater, furthers understanding of MeHg cycling in these high latitude waters and the ocean in general. Furthermore, these studies inform predictions of how climate and human interactions could influence MeHg concentrations in the Arctic region in the future.